Análise da tolerância à salinidade em plantas de sorgo, feijão-de-corda e algodão - Sousa, Carlos Henrique Carvalho de (2007)
The objective of this paper was to evaluate ions concentration and some morphophysiological parameters associates to the salt tolerance in sorghum, cowpea, and cotton plants. Plants were cultivated in plastic pots, using 15 kg of sand soil at greenhouse conditions and subjected to three different salt concentrations (0.5; 4.0; and 8.0 dS.m-1) in irrigation water. A completely randomized design, in a factorial arrangement 3 x 3 (3 species x 3 salt levels), with four replicates was adopted. During the experimental period, plant height and water use was measured. After 42 days of salt application they were measured the salinity of drained water and in the soil, total leaf area and dry masses of leaves, stems and roots. Leaf succulence, specific leaf mass, carbon partitioning and the concentrations of Na, Cl, K, Ca, and proline were also determined. The application of saline water affected the carbon partitioning, reduced plant growth and water use, and caused salt accumulation in drained water and into the soil. However, the percentage of ion extraction from the soil was low in the three species, being higher in cotton and lower in sorghum. The tolerance index, on the basis of the growth data, confirmed the highest sensibility of the cowpea and the highest tolerance of the cotton. The cotton showed some important difference to the other species, presenting greater accumulation and retention of Na and Cl in the roots, greater accumulation of these ions in the leaf blades, lower changes in K concentration and increase in proline contents in response to sat stress application. On the other hand, sorghum showed lower concentrations of potentially toxic ions (Na plus Cl) in the leaf blades. However, it also presented reductions in K and Ca contents, what can contribute to growth inhibition in this species. The high leaf Cl concentration, associated with the absence of the other protection mechanisms, contributed, at least in part, to higher sensibility of the cowpea to salt stress imposed.